The Political Career of Maria Ullfah (1934–1947) - Masrokah Masrokah; Siti Masykuroh; Uswatun Hasanah (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study examines the trajectory of Maria Ullfah’s political career from 1934 to 1947, focusing on the influence of family background and education on the formation of her political consciousness. Using historical research methods, this study presents findings showing that Maria was born into a well-educated priyayi family, which provided her with broad access to education, culminating in her legal studies at Leiden University. Her intellectual and bureaucratic environment, along with her experiences witnessing injustices faced by women, fostered social awareness and a strong commitment to addressing gender discrimination. Western education and her interactions with nationalist figures such as Sutan Sjahrir further strengthened her awareness as part of a colonized nation. After returning to Indonesia, she became actively involved in women’s organizations, educational activities, the Indonesian Women’s Congress, KOWANI, and literacy eradication efforts. During the revolutionary period, she was entrusted with important roles, including serving as a member of BPUPKI and becoming the first female Minister of Social Affairs. The findings underscore the significant role of family background, education, and personal experiences in shaping Maria Ullfah as a central figure in the women’s movement during Indonesia’s struggle for independence.